2020
DOI: 10.1021/acs.joc.9b03187
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Anion Affinities of the Canonical Organic Functional Groups

Abstract: Calculated methyl anion affinities are known to correlate with experimentally determined Mayr E parameters for individual organic functional group classes but not between neutral and cationic organic electrophiles. We demonstrate that methyl anion affinities calculated with a solvation model (MAA*) give a linear correlation with Mayr E parameters for a broad range of functional groups. Methyl anion affinities (MAA*), plotted on the log scale of Mayr E, provide insights into the full range of electrophilicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 68 publications
3
51
0
Order By: Relevance
“…[17,18] Up to now, the most predictive models have been those based on the calculation of methyl anion affinities (MAAs). [19,20] This promising approach however differs from that retained in this paper. In fact, MAA corresponds to the reaction energy of the various electrophiles with a unique selected nucleophile (CH 3…”
Section: Introductionmentioning
confidence: 83%
“…[17,18] Up to now, the most predictive models have been those based on the calculation of methyl anion affinities (MAAs). [19,20] This promising approach however differs from that retained in this paper. In fact, MAA corresponds to the reaction energy of the various electrophiles with a unique selected nucleophile (CH 3…”
Section: Introductionmentioning
confidence: 83%
“…Recently, we used QM with Density Functional Theory (DFT) simulations to investigate this problem for electron donor and electron acceptor functional groups [16,27]. Specifically, we applied DFT to over 100 diverse molecular structures and showed that in general methyl ion affinities, using a solvation model, are highly correlated to the Mayr reactivity scale.…”
Section: A Million Molecular Structuresmentioning
confidence: 99%
“…The resulting chemical reactivity scores (MCA* and MAA*), formulated as the difference between the energy of reactants and products of the reactions shown in Figure 2a, can be interpreted in slightly different ways, depending on the entity to which the score is attributed to. Van Vranken et al interpreted these quantities as the electrophilicity and nucleophilicity of the reacting functional groups [16,27]. However, in cases where only one functional group is going to react with methyl ions, the corresponding values can be attributed to the reactivity of the entire molecule.…”
Section: Reactivity Scalesmentioning
confidence: 99%
“…We propose a third and (for now) last way to exploit empirical parameter distributions. A series of theoretical models predicting Mayr-type reactivity parameters were proposed in the past [30,31,32,33,34,35,36,37,38]. The predictive power of these models was assessed with respect to some summary statistic (e.g., mean absolute error or root-meansquare error).…”
Section: Model Dispersion Vs Measurement Uncertaintymentioning
confidence: 99%